Kualitas Organoleptik Daging Kambing Yang Dimarinasi Menggunakan Jus Buah Nanas (Ananas Comosus) Dengan Waktu Yang Berbeda - Nuraisyah Nuraisyah; Suryono Suryono; Indra Sulaksana (CV. SINAR HOWUHOWU, 2026)
This study aims to determine the effect of marination time using pineapple juice on the organoleptic quality of goat meat, including color, aroma, texture, and taste. Despite its high nutritional value, goat meat is often tough with a distinctive strong odor. The bromelain enzyme in pineapple juice was tested as a natural solution to improve these traits. A Randomized Block Design (RBD) was used with four marination times: 15 minutes (P1), 30 minutes (P2), 45 minutes (P3), and 60 minutes (P4). Organoleptic testing involved 30 semi-trained panelists using a hedonic scale (1-5). Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT). The results indicated that marination time had a highly significant effect (P<0.01) on color, and a significant effect (P<0.05) on aroma and texture. However, it had no significant effect (P>0.05) on taste. In conclusion, marinating for 30 minutes was the optimal treatment, receiving the highest panelist preference. This duration effectively produced a bright red color, neutralized the strong odor, and tenderized the meat without altering its original taste.